Petőfi Sándor A hóhér kötele című regénye és az 1840-es évek bosszúprózája - Biró, Annamária (Studia Litteraria, 2024)
Sándor Petőfi’s novel, The Hangman’s Rope, published in 1846, has been a source of controversy for researchers since its publication, its position within Petőfi’s oeuvre and in the literature of the period has not been stabilised. This study attempts to discuss Petőfi’s novel not in isolation, but as an integral part of the period’s burgeoning prose literature, primarily by grouping together texts in which the concept of revenge is the main thematic component and its elaboration and its mode of execution may have prose-poetic significance. In this analysis, Petőfi’s short novel will be compared exclusively with prose works, and precisely because of its specificity in terms of length, I have tried to collect and analyse both thematically similar novels and short prose published in journals or volumes.